Long-term economic outcomes for interventions in early childhood: protocol for a systematic review - Elizabeth Geelhoed; Joelie Mandzufas; Phoebe George; Ken Strahan; Alison Duffield; Ian Li; Donna Cross (BMJ Open)
Introduction Investment in early childhood produces positive returns: for the child, the family and the community. Benefits have been shown to be significant within certain parameters, but a systematic review of the economic evidence across multiple sectors including health, education and social welfare will have the capacity to inform policy relative to the full range of social determinants. This review will take a broad approach, encompassing a range of costs and benefits to enable the identification of the most beneficial investments in early childhood and to highlight gaps in current research.Methods and analysis Economic evaluations incorporating both costs and long-term outcomes of early childhood interventions and programmes will be included. Outcomes may be valued in monetary units or quantified non-monetary units (eg, quality-adjusted life years (QALY), disability-adjusted life years (DALY)). Results will be expressed as a ratio according to the outcome; with monetary outcomes expressed as cost-benefit ratios or return on investment, and non-monetary outcomes expressed as cost per QALY or DALY. The target population is children aged 0–5 years.Extensive database searches across sectors will be undertaken. The review will involve five phases: defining the research question, identifying relevant studies, selecting studies, extracting and collating data, and summarising and reporting results. The search commenced in 2019 and the expected end date is December 2020.Ethics and dissemination The findings of this review will inform policymakers and practitioners in public health, education, social welfare and primary care settings. The publication plan includes a series of academic publications, and policy papers prepared and disseminated through Telethon Kids Institute networks. Exemption from ethics approval was granted by the University of Western Australia Human Ethics Office (RA/4/20/5677).PROSPERO registration number CRD42020145901.